Numerical Solution of Internet Pricing Scheme Based on Perfect Substitute Utility Function - Indrawati Indrawati (ICON-CSE, 2014)
In this paper we will analyze the internet pricing schemes based on Perfect Substitute utility function for homogeneous and heterogeneous consumers. The pricing schemes is useful to help internet service providers (ISP) in maximizing profits and provide better service quality for the users. The models on every type of consumer is applied to the data traffic in Palembang server in order to obtain the maximum profit to obtain optimal. The models are in the form of nonlinear optimization models and can be solved numerically using LINGO 11.0 to get the optimal solution. The results show that the case when we apply flat fee, usage-based and two part tariff scheme for homogenous we reach the same profit and heterogeneous on willingness to pay we got higher profit if we apply usage based and two part tariff schemes. Meanwhile, for the case when we apply usage based and two part tariff schemes for heterogeneous on demand, we reach better solution than other scheme.